2018
DOI: 10.1038/s41419-017-0109-1
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Fas-ligand–caveolin-1 interaction inhibits Fas-ligand translocation to rafts and Fas-ligand-induced cell death

Abstract: Fas-ligand/CD178 belongs to the TNF family proteins and can induce apoptosis through death receptor Fas/CD95. The important requirement for Fas-ligand-dependent cell death induction is its localization to rafts, cholesterol- and sphingolipid-enriched micro-domains of membrane, involved in regulation of different signaling complexes. Here, we demonstrate that Fas-ligand physically associates with caveolin-1, the main protein component of rafts. Experiments with cells overexpressing Fas-ligand revealed a FasL N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…* The first and second SH3 domains cooperate to form a common "super SH3 platform" and allow the binding of the proline-rich region of the partner protein [33]. GST pull-down assay 4th SH3 domain Ectodomain shedding, cell adhesion, and signaling [35] Cortactin [9] Co-immunoprecipitation, GST pull-down assay, immunofluorescence colocalization Unknown Regulation of actin cytoskeleton [36] CR16 [37] GST pull-down assay Weak interaction with the 2nd, 3rd, and 4th SH3 domains Reorganization of actin cytoskeleton [38] DNM2 [37] GST pull-down assay 3rd SH3 domain Endo-/exocytosis [37] FasL (CD178) [39] Phage display screening 3rd and 4th SH3 domains Apoptosis induction [40] GRB2 [28] Affinity purification-selected reaction monitoring mass spectrometry…”
Section: Egfr Signaling Via Tks4 and Tks5mentioning
confidence: 99%
See 3 more Smart Citations
“…* The first and second SH3 domains cooperate to form a common "super SH3 platform" and allow the binding of the proline-rich region of the partner protein [33]. GST pull-down assay 4th SH3 domain Ectodomain shedding, cell adhesion, and signaling [35] Cortactin [9] Co-immunoprecipitation, GST pull-down assay, immunofluorescence colocalization Unknown Regulation of actin cytoskeleton [36] CR16 [37] GST pull-down assay Weak interaction with the 2nd, 3rd, and 4th SH3 domains Reorganization of actin cytoskeleton [38] DNM2 [37] GST pull-down assay 3rd SH3 domain Endo-/exocytosis [37] FasL (CD178) [39] Phage display screening 3rd and 4th SH3 domains Apoptosis induction [40] GRB2 [28] Affinity purification-selected reaction monitoring mass spectrometry…”
Section: Egfr Signaling Via Tks4 and Tks5mentioning
confidence: 99%
“…Adaptor protein involved in the regulation of RTK signaling, cycle progression, actin-based cell motility, podosome formation [41] NOXA1 [42,43] Co-immunoprecipitation, GST pull-down assay Unknown ROS generation through NOX1 activation [44] [35] Cortactin [9] Co-immunoprecipitation, GST pull-down assay, immunofluorescence co-localization Unknown Regulation of actin cytoskeleton [36] CR16 [37] GST pull-down assay Weak interaction with the 2nd, 3rd, and 4th SH3 domains Reorganization of actin cytoskeleton [38] DNM2 [37] GST pull-down assay 3rd SH3 domain Endo-/exocytosis [37] FasL (CD178) [39] Phage display screening 3rd and 4th SH3 domains Apoptosis induction [40] NOXA1 [42,43] Co-immunoprecipitation, GST pull-down assay Unknown ROS generation through NOX1 activation [44] N-WASP [37] GST pull-down assay 2nd SH3 domain A scaffold protein regulating actin cytoskeleton reorganization, and actin polymerization during cell motility and invasion [45] OPHN1 [37] GST pull-down assay 3rd SH3 domain Endo-/exocytosis [37] RUK/CIN85 [46] GST pull-down assay Unknown…”
Section: Unknownmentioning
confidence: 99%
See 2 more Smart Citations
“…Cav-1 KO disrupted death-induced signaling complex formation following colocalization and interaction between cav-1 and Fas [150]. Recently, Glukhova et al found that the deletion of both caveolin-binding sites (which bind the N-terminal domain and B-terminal domain of cav-1) in the Fas-ligand attenuated extrinsic cell death pathway-associated cytotoxicity, demonstrating that the relationship between the Fas-ligand and cav-1 provides a molecular basis for the location of the ligand to lipid rafts and Fas-ligand-dependent apoptosis [151]. As for the intrinsic apoptosis pathway, mitochondrial outer membrane permeabilization is the central event of the intrinsic pathway: in response to apoptotic stimuli, mitochondria release intermembrane space proteins, such as cytochrome C and apoptosis-inducing factor, which exert a cryptic cytotoxic activity following their mitochondrial release [152].…”
Section: Important Role Of Cav-1 In Ismentioning
confidence: 99%